Penerapan Metode Economic Order Quantity Pada Rancangan Aplikasi Inventory Control System - Stela Veranita Anwar; Mercurius Broto Legowo (Ikatan Ahli Informatika Indonesia (IAII), 2018)
The purpose of this research is the application of EOQ method in designing inventory control system application to control inventory in case study in Damkar Sub-Dept. of Warehouse Section - South Jakarta area. This research is carried out the existence of various inventory control problems, such as: uneconomical inventory control, unsafe stock, and difficult re-ordering. Then, to resolve the various issues in inventory control, it is necessary to apply the EOQ method in the inventory control system application. The design of system application in this research by using Unified Modeling Language (UML) approach. The results of this applied product research is a system application that allows system users to be able to control their inventory quickly, easily and accurately and provide reports in the form of graphs that are very helpful in decision making. The application of this system will be a very useful tool for optimal inventory control. This system application is expected to be a very useful tool for optimal inventory control.